Meso research on the mechanical properties of rock specimens with double prefabricated circular holes based on digital image correlation - Chen, Nengbin; Zhou, Yu; Gao, Yongtao; Sun, Zheng; Wang, Li (Kuwait Journal of Science, 2020)
Based on digital image correlation technology (DIC) and acoustic emission technology, combined with particle flow theory and PFC program, the crack propagation law of rock samples with double pre-existing holes under uniaxial compression and the damage and failure process of rocks were studied systematically. The main findings are as follows: (1) In the early stages of the test loading, as the load increases, it can be found from the evolution of the cloud diagrams that the strain is transferred from the initial distribution around the prefabricated circular holes to the upper and lower ends of the prefabricated circular holes, and gradually extends outward along the vertical direction. (2) During the period from the stable expansion phase of the crack to the nonstable expansion phase, when the stress-strain curve has a stress drop, it is accompanied by a sharp increase in the number of acoustic emission events. In addition, the greater the absolute value of the stress drop, the greater the frequency of acoustic emission events. (3) Obvious "anti-symmetric" features are exhibited in both the horizontal and vertical displacement fields; the left side of the horizontal displacement field is negative and the right side is positive; the displacement of the vertical displacement field is distributed in a V-shape upward and downward at the center of the round hole, respectively. (4) The DIC technique can be used to quantitatively describe the evolution of the crack displacement field and strain field in the process of rock failure, providing a more intuitive and accurate way for the study of crack evolution.